2012
DOI: 10.1242/jeb.054395
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and cutaneous water loss of birds

Abstract: ) below the surface of the skin, assumed to be at saturation at skin temperature,  a is absolute humidity above the skin and r v is the total resistance to vapor diffusion. Total resistance is a composite of the resistances of the skin, the boundary layer and the feathers, although the contribution of feathers and boundary layer Summary There is a crucial need to understand how physiological systems of animals will respond to increases in global air temperature. Water conservation may become more important fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Weathers and Caccamise (1978) investigated seasonal changes in the thermal physiology of Monk Parakeets (Myiopsitta monachus) and found that TEWL at T a ≈ 20 -30 °C was lower in winter, a result the authors related to reduced water availability in winter. Several workers have found that birds can significantly augment CEWL through changes in water vapour diffusion resistance via alterations in the composition of lipids in the stratum corneum (Haugen et al 2003;Muñoz-Garcia et al 2008;Williams et al 2012). Arad et al (1987), for example, observed an overall reduction in TEWL in dehydrated pigeons at T a ≈ 45 °C due to reductions in CEWL.…”
Section: Evaporative Water Lossmentioning
confidence: 99%
“…Weathers and Caccamise (1978) investigated seasonal changes in the thermal physiology of Monk Parakeets (Myiopsitta monachus) and found that TEWL at T a ≈ 20 -30 °C was lower in winter, a result the authors related to reduced water availability in winter. Several workers have found that birds can significantly augment CEWL through changes in water vapour diffusion resistance via alterations in the composition of lipids in the stratum corneum (Haugen et al 2003;Muñoz-Garcia et al 2008;Williams et al 2012). Arad et al (1987), for example, observed an overall reduction in TEWL in dehydrated pigeons at T a ≈ 45 °C due to reductions in CEWL.…”
Section: Evaporative Water Lossmentioning
confidence: 99%
“…Ecological aspects of thermoregulatory performance in doves and quail Williams et al (2012) has suggested that desert birds need the capacity to increase EWL during periods of extreme heat in order to maintain sub-lethal T b , while minimizing dehydration over the long term. In this study, we found that the thermoregulatory performance and water balance of mourning and white-winged doves differed greatly from that of the sympatric Gambel's quail.…”
Section: Body Temperature and Heat Tolerance Limitmentioning
confidence: 99%
“…Estimates calculated from the difference between water gain and cloacal fluid output have also yielded high EWL values for sunbirds and honeyeaters (Collins, 1981;Fleming and Nicolson, 2003;Lotz and Nicolson, 1999). Nothing is known of the partitioning of evaporation between cutaneous and respiratory routes, but cutaneous EWL is influenced by hydration state in other birds (Williams et al, 2012). Unfortunately, the high excretory output of avian nectarivores complicates the direct measurement of EWL, and the pharmacokinetic method has proved unreliable for its estimation (Purchase et al, 2013b).…”
Section: The Potential Role Of Evaporationmentioning
confidence: 99%